ДИФФЕРЕНЦИАЛЬНАЯ ЭНДОРЕДУПЛИКАЦИЯ ХРОМОСОМ КАК ДОПОЛНИТЕЛЬНЫЙ СПОСОБ КОДИРОВАНИЯ НАСЛЕДСТВЕННОЙ ИНФОРМАЦИИ У РАСТЕНИЙ (ТЕОРЕТИЧЕСКАЯ МОДЕЛЬ) (Experimental biology, 2009)
Hypothesis about role of differential chromosomal endoreduplication in encoding of inherited information in plants is presented. This hypothesis was originated on the base of experimental and literary data.
Keywords: endoreduplication